COMPARISION OF LIPID EXTRACTION EFFECTIVENESS FROM Sargassum oligocystum ALGAE BY ENZYME AND ULTRASOUND METHODS - Vo Phan Tuan Vu; Tran Thi Yen Nhi; Nguyen Ngoc Thu; Thanh Hoang Phi Yen; Hoang Thi Ngoc Nhon (HUIT Journal of Science, 2023)
This study aimed to examine the effects of enzyme and ultrasound on lipid extraction from Sargassum oligocystum algae. The enzyme-assisted extraction conditions of lipid with the enzyme included: enzyme ratio (0, 0.5, 1, 1.5, and 2 v/w), pH (3.5, 4, 4.5, 5, and 5.5), temperatures (35, 40, 45, 50, and 55 ℃) and extraction time (60, 90, 120, 150, and 180 min). The investigation of lipid extraction parameters from S. oligocystum algae using ultrasonic waves, such as material/solvent ratio (1/5, 1/10, 1/15, 1/20, and 1/25 w/v), time (5, 10, 15, 20, and 25 min). The results showed that the suitable conditions for lipid extraction with Viscozyme L were an enzyme concentration of 1.5%, pH 4.5, at 50 ℃ for 150 min. The results show that the recovery efficiency of lipid extraction from S. oligocystm algae using shaking method combined with Viscoenzyme L treatment (48.17 ± 0.91%) was higher than the that of ultrasound method (46.88 ± 1.03%).